Monomethyl Fumarate (MMF, Bafiertam) for the Treatment of Relapsing Forms of Multiple Sclerosis (MS) - Amnon A. Berger; Emily R. Sottosanti; Ariel Winnick; Jonathan Izygon; Kevin Berardino; Elyse M. Cornett; Alan D. Kaye; Giustino Varrassi; Omar Viswanath; Ivan Urits (MDPI AG, 2021)
Multiple sclerosis (MS) is a prevalent neurologic autoimmune disorder affecting two million people worldwide. Symptoms include gait abnormalities, perception and sensory losses, cranial nerve pathologies, pain, cognitive dysfunction, and emotional aberrancies. Traditional therapy includes corticosteroids for the suppression of relapses and injectable interferons. Recently, several modern therapies-including antibody therapy and oral agents-were approved as disease-modifying agents. Monomethyl fumarate (MMF, Bafiertam) is a recent addition to the arsenal available in the fight against MS and appears to be well-tolerated, safe, and effective. In this paper, we review the evidence available regarding the use of monomethyl fumarate (Bafiertam) in the treatment of relapsing-remitting MS.